Development of bioprocesses based in biphasic media involving the yeast Yarrowia lipolytica - Gomes, Nelma (2008)
Yarrowia lipolytica has been intensively used in our research group to develop different bioprocesses based in the ability of this yeast to use hydrophobic substrates. Work has been focused in the optimization of the production of y-decalactone and lipase, and to degrade and detoxify olive oil wastewater producing simultaneously high-value compounds, such as enzymes. Studies of the oxygen mass transfer phenomenon in biphasic media was also conducted and applied to select the most adequate oxygenation conditions for bioprocesses. Application of increased air pressures has also been proven to be an effective mean to improve oxygen transfer rate into Y. lipolytica cultures.